Lysosome-Dependent Activation of Human Dendritic Cells by the Vaccine Adjuvant QS-21 - Welsby, Iain; Detienne, Sophie; N’Kuli, Francisca; Thomas, Séverine; Wouters, Sandrine; Bechtold, Viviane; De Wit, Dominique; Gineste, Romain; Reinheckel, Thomas; Elouahabi, Abdelatif; Courtoy, Pierre J.; Didierlaurent, Arnaud M.; et al. (Frontiers in Immunology, 2017)
The adjuvant properties of the saponin QS-21 have been known for decades. It is a component of the Adjuvant System AS01 that is used in several vaccine candidates. QS-21 strongly potentiates both cellular and humoral immune responses to purified antigens, yet how it activates immune cells is largely unknown. Here we report that QS-21 directly activated human monocyte-derived dendritic cells (moDCs) and promoted a pro-inflammatory transcriptional program. Cholesterol-dependent QS-21 endocytosis, followed by lysosomal destabilisation and Syk kinase activation were prerequisites for this response. Cathepsin B, a lysosomal cysteine protease, was essential for moDC activation in vitro and contributed to the adjuvant effects of QS-21 in vivo. Collectively, these findings provide new insights into the pathways involved in the direct activation of antigen-presenting cells by a clinically relevant QS-21 formulation.